PENGARUH PARTISIPASI PENGANGGARAN, ASIMETRI INFORMASI, BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI PADA SENJANGAN ANGGARAN - Dianthi, Ida Ayu Gede Purba; Wirakusuma, Made Gede (E-Jurnal Akuntansi; Vol 18 No 2 (2017), 2017)
Budgeting participation in the budgeting process of a company can cause dysfunctional behavior of the manager, the manager tends to create a budget gap. Managers who participated in the drafting process of budgeting can experience role ambiguity will encourage managers raises the budget gap. This study aims to determine the effect of participation budgeting, information asymmetry, organizational culture, and organizational commitment on budgetary slack in the General Hospital of Badung Mangusada. This research was conducted by survey method using a questionnaire. The samples were analyzed by 50 respondents using purposive sampling technique sampling. The analysis technique used in this research is multiple linear regression analysis. The research proves that partipasipasi budgeting and information asymmetry positive influence on budgetary slack while culture and organizational commitment negatively affect the budgetary slack in the General Hospital of Badung Mangusada.
Keywords: Participation Budgeting; budgetary slack; Information Asymmetry; Organizational Culture; Organizational Commitment